Relationship between Resting and Recovery Heart Rate in Horses - Lindner, Arno (2020)
In endurance racing the heart rate (HR) of horses in the veterinary gates has to reach a maximum set to continue racing. There is no literature on the relationship between resting HR (HRresting) and HR after exercise (HRrecovery). This relationship was examined in seven horses and the results were related to their v4 (speed at which the blood lactate concentration is 4 mmol/L). Horses were submitted to an exercise test to determine v4. Thereafter, horses were exercised on a treadmill in randomized order for 10 and 60 min at different speeds. HR was measured before exercise and several times until 30 min of recovery. The relationship between HRresting and HRrecovery was significant in 16 out of 35 comparisons. There were no significant relationships between the v4 of the horses and their HRresting and between v4 and HRrecovery after 10 min of exercise, regardless of the speed of exercise, with one exception. The relationship between the v4 of the horses and their HRrecovery after 60 min of exercise was significant in the fifth minute after exercise at 3.5 m/s only. Conclusion: Because HRresting and HRrecovery are often related, pre-determined arbitrary HRrecovery values may not allow for fair competition during endurance racing.